Front Cover: A poly(dimethylsiloxane) microfluidic sheet reversibly adhered on a glass plate for creation of emulsion droplets for droplet digital PCR. Issue 2 (16th January 2017) - Nakashoji, Yuta; Tanaka, Hironari; Tsukagoshi, Kazuhiko; Hashimoto, Masahiko
Abstract : Electrophoresis 2017, 38, 296–304. DOI:10.1002/elps.201600309 The cover picture shows some major steps in the workflow of our droplet digital PCR platform. A poly(dimethylsiloxane) (PDMS) microfluidic chip with T‐junction channel geometry was reversibly adhered on a glass plate through the viscoelastic properties of PDMS. This formed a detachable microfluidic device for creation of water‐in‐oil droplets that were used as discrete reaction partitions for the droplet digital PCR. Our droplet preparation technique only required evacuation of air dissolved in the PDMS before loading oil and aqueous phase into separate inlet reservoirs. Because the PDMS chip can be peeled off the glass plate, blocked channels can easily be fixed when they arise. The fluorescence analysis of thermally cycled droplet samples showed that the proportions of positive partitions (i.e., fluorescent droplets) followed the Poisson distribution.